Microfinance s Impact on Education, Poverty, and Empowerment: A Case Study from the Bolivian Altiplano - Sarah Gibb (Institute for Advanced Development Studies (INESAD), 2008)
This study explores the impact of microcredit on economic, educational, and empowerment levels of women from the Bolivian high plains who had acquired microcredit for over three years. Primary research was carried out with the help of a major NGO dedicated solely to microcredit. 100 in-depth personal interviews were conducted by the author in La Paz and El Alto from February to May 2007. This region was chosen because of the wide extent to which microcredit have been implemented here since the 1980s. The author created a control group from women who had never taken out a microcredit. The study employs the use of an established poverty scorecard to measure poverty levels over time. Using a comparative approach that allows a comparison between the independent control group and the loan group, the study finds that while the ownership of goods increased in the loan group, the benefits of microcredit on family educational attainment levels and empowerment are questionable. It is important to note that the vast majority of microcredit research does not use this type of independent control group.
Keywords: Z13; 330; Microcredit; microfinance; empowerment; development; women; Bolivia.